Presumed consent for organ donation: illusion of a choice - Dar, Reeta (International Journal Of Community Medicine And Public Health, 2016)
India has been following informed consent (opt- in) system of organ donation but soft pressures to shift to presumed consent (opt- out) system are simultaneously palpable. This paper describes presumed consent briefly and explains why the need to shift to this system is felt. The paper challenges the morality of presumed consent system and describes its use as absolutely unethical in view of socio cultural diversity, educational disparity and profound class stratification of our country. The paper throws some light on our own system which, unlike other countries, is not ready for this change. It focuses on thought-provoking issues that are deterrents to achieving increase in organ donation even if presumed consent system is adopted in India. It reflects the outcome of this coercive legal option in some countries. In some countries there was no change in organ donation rates. A few countries witnessed negative repercussions of presumed consent system. Some of these countries had no option except to revert back to opt- in system. The paper tries to give a message to the public and professionals by comparing Spain to India that has high donation rates in the world not because of presumed consent but because of other contributory factors. Spain initiated organ donation and transplant activities much ahead of India and their healthcare services are rated the best in the world. Socio-cultural, religious and political milieu unlike India is conducive to organ donation in Spain. Adequate investments in public health, adequate budget for organ donation and transplantation, excellent infrastructure, availability of public health assistance to 99% population, adequate availability of ICU beds, extending end of life care to all, positive approach to organ donation by majority of people, thorough professionalism and public trust is what makes Spain the best country in organ donation. The same is lacking in India. The paper warns us of this coercive option by drawing a parallel to the coercions that took place when India acted coercively to control population through compulsory sterilization and led to the wrath of masses in 1976. India as on date needs to focus on other issues to increase organ donation rates like development of infrastructure, developing well-functioning national, regional and state level organizations, building in trust of people, identifying potential donors, managing donors, caring for donor families, training manpower, increasing awareness on organ donation and transplantation, reimbursing fees to organ retrieval hospitals, merging efforts of various stakeholders, developing transparent and workable organ sharing policies and regular auditing of brain stem deaths.